Предмет: Математика,
автор: ctefanzova
15 7/9+10 3/9-(6 2/3-4 2/3)
Ответы
Автор ответа:
0
Если что-то будет не понятно я объясню.
Приводим 4/3 к общему знаменателю 9 и получаем 12/9
Приводим 4/3 к общему знаменателю 9 и получаем 12/9
Автор ответа:
0
15 7/9 + 10 3/9 - (6 2/3 - 4 2/3) = 24 1/9
1) 6 2/3 - 4 2/3 = 2
2) 15 7/9 + 10 3/9 = 25 10/9 = 26 1/9
3) 26 1/9 - 2 = 24 1/9
1) 6 2/3 - 4 2/3 = 2
2) 15 7/9 + 10 3/9 = 25 10/9 = 26 1/9
3) 26 1/9 - 2 = 24 1/9
Похожие вопросы
Предмет: Литература,
автор: Katamiftieva
Предмет: Обществознание,
автор: qadrizadez
Предмет: Французский язык,
автор: Dimongzr
Предмет: Алгебра,
автор: coldness
Предмет: Биология,
автор: nataly0695